Feeding dried distillers grains with solubles to lactating beef cows: impact of excess protein and fat on cow performance, milk production and pre-weaning progeny growth - Shee, C. N.; Lemenager, R. P.; Schoonmaker, J. P. (Animal (Cambridge, England), 2016)
Multiparous Angus×Simmental cows (n=54, 5.22±2.51 years) with male progeny were fed one of two diets supplemented with either dried distillers grains with solubles (DDGS) or soybean meal (CON), from calving until day 129 postpartum (PP) to determine effects of excess protein and fat on cow performance, milk composition and calf growth. Diets were formulated to be isocaloric and consisted of rye hay and DDGS (19.4% CP; 8.76% fat), or corn silage, rye hay and soybean meal (11.7% CP; 2.06% fat). Cow–calf pairs were allotted by cow and calf age, BW and breed. Cow BW and body condition score (BCS; P⩾0.13) were similar throughout the experiment. A weigh-suckle-weigh was performed on day 64 and day 110±10 PP to determine milk production. Milk was collected on day 68 and day 116±10 PP for analysis of milk components. Milk production was unaffected (P⩾0.75) by dietary treatments. Milk urea nitrogen was increased at both time points in DDGS compared with CON cows (P<0.01). Protein was decreased (P=0.01) and fat was increased (P=0.01) in milk from DDGS compared with CON cows on day 68 PP. Compared to CON, DDGS decreased medium chain FA (P<0.01) and increased long chain FA (P<0.01) at both time points. Saturated FA content of milk was decreased (P<0.01) at both time-points in DDGS compared with CON cows, which resulted in an increase (P<0.01) in monounsaturated and polyunsaturated FA, including cis-9, trans-11 conjugated linoleic acid. Daily gain of the DDGS calves was increased (P=0.01) compared with CON calves, resulting in heavier BW on day 129 (P=0.01). Heavier BW of DDGS calves was maintained through weaning (P=0.01). Timed-artificial insemination (TAI) rates were greater for cows fed DDGS compared with cows fed CON (P<0.02), but dietary treatment had no effect on overall pregnancy rates (P=0.64). In summary, feeding DDGS to lactating beef cows did not change cow BW or BCS, but did improve TAI rates and altered milk composition compared with CON. As a result, male progeny from cows fed DDGS during lactation had greater average daily gain and were heavier at day 129 and at weaning compared with male progeny from cows fed a control diet.